ANALISIS SEM PADA ONLINE CUSTOMER REVIEW DAN CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN - Lidia Afriani Banurea; Anne Rumondang Malau; Pantas H Silaban; Leonardo Davidsi Sipayung (Jurnal Bina Bangsa Ekonomika, 2023)
This research aims to determine the influence of online customer reviews and online customer ratings on the purchase decision of Wardah Skincare products on the shopee marketplace through consumer trust. The respondents used in this study were women and men aged 17 years who were domiciled in the city of Medan and had purchased wardah skincare products on the shopee marketplace and filled out online customer reviews and online customer ratings. After collecting data, the sample used in this study was 100 respondents with purposive sampling method with non-probability sampling technique. The results of the analysis show that online customer reviews and online customer ratings do not have a significant influence on purchasing decisions. Online customer reviews have no influence on consumer confidence while online customer ratings have a significant effect on consumer confidence. Consumer trust has a significant influence on purchasing decisions. The influence of online customer reviews on purchasing decisions through consumer trust is not significant while online customer ratings on purchasing decisions through consumer trust have a significant influence. The data analysis used in this study is through a structural equation modeling approach / Structural Equation Model (SEM) using Smart-PLS 3.0 software